Current and future prospects of small hydro power in Pakistan: A survey. (April 2019) - Uddin, Waqar; Ayesha,; Zeb, Kamran; Haider, Aun; Khan, Bilal; Islam, Saif ul; Ishfaq, M.; Khan, Imran; Adil, M.; Kim, Hee Je
Abstract: Currently, the electrical energy crisis is an important issue in Pakistan. Due to the shortage of electrical power, inhabitants of the country are facing 10–12 h of blackouts in urban areas and 14–20 h in rural areas daily. The current demand for electrical power is 15, 000 MW, which is expected to increase further to 49, 078 MW by 2050. Conventional energy sources are unable to meet this demand. This paper discusses the potential of Small Hydro Power Plants (SHPPs) to partially overcome the shortage of electricity. Overall, 60, 000 MW of hydroelectric resources have been identified in Pakistan. whereas, approximately 11% of the identified resources are operational, producing 7228 MW of electric power. The energy crisis can be easily overcome by installing SHPPs. The use of SHPPs has been estimated to save 120 million tons of coal or 83.3 billion liters of oil in a year. Thus, these plants are environmentally friendly and make a low contribution to global warming. Worldwide, SHPPs provide employment to 0.2 million people. Pakistan Council of Renewable Energy Technology (PCRET) and Sarhad Rural Support Program (SRSP) has installed 1100 SHPPs, with a total capacity of 42.507 MW, which fulfills the electrical energy demand of approximately 0.7 million people in Pakistan. Highlights: 1. It focuses on current Energy Crisis in Pakistan, where the inhabitant faces 14–20 h of load shedding. 2. The paper describes the available and installed potential of hydro power. Its show a high gap that needs to be filled. 3. The paper emphasis on the full utilization of available hydro resources to mitigate the energy crisis. 4. A section of paper highlighted the "Barrier occurs during installation of new plants". That needs to address to promote the green energy 5. It also summarizes the effect of small hydro plant on environment. The effects of different renewable energy resources are compared in the section 6. The hydropower is also compared on the bases of its economic benefits and other social benefits.